2013
DOI: 10.1155/2013/629092
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Morphological Characterization of PLA/Chitosan/Epoxidized Natural Rubber Composites

Abstract: Poly (lactic acid) (PLA)/chitosan (CS) natural polymer/epoxidised natural rubber (ENR) composites were successfully prepared through a solution casting method. The morphological characteristics of fabricated composites were investigated by scanning electron microscopy (SEM) and optical microscopy. The microstructure of PLA/ENR was significantly altered with the addition of CS. SEM analysis of composites fractured surfaces revealed smooth and homogeneous texture and good dispersion of CS. However for 15 wt% CS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 30 publications
4
44
0
Order By: Relevance
“…So, it can be anticipated that future developments will keep including blends of PLA, copolymers, and impact-modified products, which will also further expand the applications where this unique polymer can be used. Besides that, we do expect for the nearby future increasing research interest in the following four areas: a) PLA blends stability: recently, several PLA blends based synthetic or natural components have been reported and found very efficient in PLA properties improvement [235,[330][331][332][333][334][335][336][337][338][339][340][341][342][343]. However, very limited attention have been given for studying blends stability under different aging conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, it can be anticipated that future developments will keep including blends of PLA, copolymers, and impact-modified products, which will also further expand the applications where this unique polymer can be used. Besides that, we do expect for the nearby future increasing research interest in the following four areas: a) PLA blends stability: recently, several PLA blends based synthetic or natural components have been reported and found very efficient in PLA properties improvement [235,[330][331][332][333][334][335][336][337][338][339][340][341][342][343]. However, very limited attention have been given for studying blends stability under different aging conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In this area, we have also found that less attention has been given to inorganic nano-particles while various have been recognized as possible additives to enhance the polymer performance, their potential in combination with PLA should be further studied. c) Composites of fiber mixtures: such mixtures combine the positive properties of different fibers [334][335][336][337][338][339][340][341][342][343].…”
Section: Discussionmentioning
confidence: 99%
“…It is typical to accept that there was no interaction between a plasticizer and a thermoplastic when the FTIR spectra remained unchanged upon addition (Maizatul et al 2013), while a minute shift or peak intensity change can provide evidence of possible interaction between the materials (Al-Mulla et al 2014;Silverajah et al 2012;Zakaria et al 2013).…”
Section: Ftir Spectramentioning
confidence: 99%
“…PLA eventually disintegrates into harmless components, such as carbon dioxide, water, and other nontoxic small molecules under compost conditions in landfills . It can be used in a variety of applications owing to its several advantages such as high tensile strength, elastic modulus and transparency, good processing performance, recyclability, and environmentally friendly characteristics . Additionally, PLA can be fabricated by many standard plastic processes, including injection, compression and blow molding, extrusion, thermoforming, and film forming .…”
Section: Introductionmentioning
confidence: 99%